Trained and Non-Trained Language Teachers on CLIL Methodology: Teachers' Facts and Opinions about the CLIL Approach in the Primary Education Context in Spain - Gema Alcaraz-Mármol (Universidad de La Sabana, 2018)
Since the early 2000s, there seems to be a growing interest in bilingual education in Spain. The need for teachers with certain accreditation in foreign language proficiency has been growing in the last decade. Yet, the methodological basis to integrate content and language in the classroom does not seem to be a compulsory requirement. The participants of this study were surveyed about several aspects of their teaching practice. We compared the answers of those who have received specific methodological CLIL training and those who have not. Results show that methodological training beyond just foreign language teaching makes significant differences in terms of the teachers' opinions on CLIL and practice of using bilingual practices in their classrooms, making use of a wider variety of activities and resources. Differences were found in the way they see their own teaching, their use of their L1, materials in the classroom, and the variety and type of activities they develop with their students.